ENTERPRISE RESTRUCTURING AIM AND TYPES - S. P. Baranenko; V. O. Nikonov (Модернизация, инновация, развитие, 2016)
Enterprise restructuring is aimed at adapting it to market conditions and improving its competitiveness through selection of most effective model of using material, technical, technological, organizational, commercial, economical, financial, tax-related and other resources with due account of the demand. Restructuring classification signs and types as well as restructuring aims specific for industrial enterprises are provided for.